A Study on the Design and Effectiveness of a Spoken English Program for Gujarati Medium Secondary School Students (Aged 14–15) - Jakhotra, Maheshbhai R.; Gupta, Sanjay (The Scientific Temper, 2025)
To accomplish the objectives of this project, an English language program will be designed, developed, and evaluated for Gujarati children aged 14 to 15 years old who do not attend school in an English medium. Utilizing a pre-experimental one-group pre-test post-test methodology, the curriculum was evaluated in three different educational institutions of varying sizes. A spoken English exam that was specifically designed to gather information was used to evaluate the individual’s vocabulary, grammar, pronunciation, comprehension and fluency. The intervention resulted in a significant improvement in the students’ spoken English ability, with significant disparities seen between the students based on gender.There was not real difference found in Spoken English proficiency between the students from urban and rural areas. According to the findings of the study, children in secondary schools who speak other regional languages may benefit from participating in planned spoken English therapy. It is the goal of these treatments to enhance the student’s ability to communicate verbally.